Effect of varnish containing casein phosphopeptides-amorphous calcium phosphate and fluoride on surface microhardness of enamel - An in vitro study - K L Girish Babu; Priya Subramaniam; Sangeeta Teleti (Wolters Kluwer Medknow Publications, 2020)
Background: Fluoride varnish is one of the professionally applied topical fluoride agents. The ease of application of fluoride varnishes has led to its popularity in pediatric dentistry. Aim: The aim of the study is to evaluate and compare the effect of varnish containing casein phosphopeptides-amorphous calcium phosphate (CPP-ACP) and fluoride (MI Varnish®) with that of varnish containing only fluoride (Fluor Protector®) on surface microhardness (SMH) of enamel. Materials and Methods: Enamel blocks were cut from the 90 premolar teeth samples. The samples were divided into three Groups (A, B, and C) consisting of 30 blocks each. Varnish containing CPP-ACP with fluoride was applied on samples of Group A and varnish containing only fluoride was applied on the samples of Group B. Group C was used as control group; without any varnish application. After varnish application, these samples were subjected to pH cycling. Following, SMH was assessed using SMH tester machine. Results: The mean values of SMH for Group A were 488 ± 6 vickers hardness number (VHN), Group B were 485 ± 12 VHN, and Group C were 448 ± 12 VHN. Conclusion: There was no significant difference in the SMH of enamel between the varnish containing CPP-ACP and fluoride, with that of varnish containing only fluoride.